Simulation of photoelectron spectra using the reflection principle in combination with unrestricted excitation ADC(2) to assess the accuracy of excited-state calculations - Knippenberg, Stefan; Dreuw, Andreas (ChemPhysChem, 2011)
The gas-phase photoelectron spectra of ethene, formaldehyde, formic acid and difluoromethane are simulated using the reflection principle and the unrestricted second-order algebraic diagrammatic construction [UADC(2)] scheme of the polarization propagator for the computation of the vertical-excited states of the cations at the equilibrium geometry of the parent neutral molecule. Comparison is made with experimental spectra and the established highly accurate ionization IP-ADC(3) theory to gain insight into the accuracy and applicability of recently developed excitation UADC schemes. Within UADC(2), we distinguish between the strict and extended schemes UADC(2)-s and UADC(2)-x. While the latter approach is found to slightly underestimate the experimental photoelectron spectra by 0.3 eV and can thus be regarded as a reliable scheme within the limits of the applied reflection principle and the underlying approximations, the UADC(2)-s scheme tends to overestimate the excitation energies by about 0.5 eV. Time-dependent density functional theory is also applied in combination with the standard B3LYP xc functional and turns out to be a useful computational tool for the simulation of the photoelectron spectra of the studied species.